Inventarisasi Tumbuhan Obat Tradisional dan Pemanfaatannya di Kecamatan Kahayan Tengah Kabupaten Pulang Pisau: Inventory of Traditional Medicinal Plants and Their Uses in Kahayan Tengah Subdistrict Pulang Pisau Regency - Ludang, Yetrie; Luhan, Gimson; Jaya, Herry Palangka (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2025)
Traditional medicine knowledge of the Dayak Ngaju tribe in Kahayan Tengah District, Pulang Pisau Regency still utilizes and uses plants as one of the traditional medicines to cure diseases and maintain health. The study aims to inventory medicinal plants of the Dayak Ngaju tribe in Kahayan Tengah District, document and explore local wisdom related to their use. Qualitative methods through in-depth interviews were used to obtain primary data. Respondents were selected using purposive sampling techniques with the criteria being people working as traditional healers as many as 5 people from selected villages/sub-districts as key figures. The results of the study showed that the types of plants used as traditional medicine by the Dayak Ngaju tribe in Kahayan Tengah District, Pulang Pisau Regency amounted to 130 types including 56 families, the dominance of the most types of plants for treatment from the Myrtaceae family 9 types (6.9%). The most widely used plant habitus is in the form of trees 50 types (38%), the most widely used plant parts are in the form of leaves as many as 79 species (32%). The most common way of processing/using plants is by boiling and drinking them, as many as 107 types (58%), and the most widely used type of plant as medicine based on disease classification is chronic disease, as many as 174 types (51.03%).